Bepridil enhances aprindine-induced prolongation of atrial effective refractory period in a canine atrial rapid pacing model. Issue 5 (November 2015) - Nakatani, Yosuke; Sakamoto, Tamotsu; Nishida, Kunihiro; Kataoka, Naoya; Yamaguchi, Yoshiaki; Sakabe, Masao; Fujiki, Akira; Mizumaki, Koichi; Inoue, Hiroshi
Abstract Background Bepridil in combination with aprindine could restore sinus rhythm in patients with persistent atrial fibrillation (AF). The present study aimed to investigate the electrophysiological mechanisms of the combined effects of bepridil and aprindine. Methods Subjects consisted of 6 dogs without and 6 dogs with atrial rapid pacing (ARP) carried out at 400 bpm for 2 weeks. Bepridil was administered for 1 week in both groups (ARP dogs were administered bepridil in the second week). The electrophysiological effects of the intravenous administration of aprindine (1 mg/kg) were evaluated before and after the administration of bepridil. Results In non-paced dogs, the atrial effective refractory period (AERP) became longer after the administration of bepridil (from 151 ± 10 ms to 170 ± 7 ms, p < 0.05); however, no additional AERP prolongation was observed after the acute administration of aprindine. In ARP dogs, the AERP shortened with ARP for a week, and tended to lengthen after the administration of bepridil (from 93 ± 5 ms to 118 ± 9 ms, p = 0.08). In these dogs, the acute aprindine administration did not prolong the AERP before the administration of bepridil, although it did after the administration of bepridil (from 118 ± 9 ms to 142 ± 8 ms, p < 0.01). AF duration did not change after the administration of bepridil, although it shortened significantly after the additional administration of aprindine (from 2.2 ± 0.3 s to 1.4 ± 0.8 s, p < 0.05). Conclusions Bepridil enhances the effect of aprindine for the prevention of AF by reversing atrial electrical remodeling.